Measurement of leading proton and neutron production in deep-inelastic scattering at HERA - Adloff, C; Anderson, M; Andreev, V; Andrieu, B; Arkadov, V; Arndt, C; Ayyaz, I; Babaev, A; Bahr, J; Baranov, P; Barrelet, E; Bartel, W; et al. (1999)
The production of leading neutrons, where the neutron carries a large fraction xL of the incoming proton's longitudinal momentum, is studied in deep-inelastic positron-proton scattering at HERA. The data were taken with the H1 detector in the years 2006 and 2007 and correspond to an integrated luminosity of 122 pb-1. The semi-inclusive cross section is measured in the phase space defined by the photon virtuality 6